Strategic objectives and development plans of beginning farmers - Rantamäki-Lahtinen, Leena; Väre, Minna (MTT Agrifood Research Finland, 2012)
Taking over the management and ownership of a farm contributes positively to farm growth but little is known about how farmers succeed after the starting phase. We analysed how farmers that have recently started their farm enterprises are going to develop their farms and how do they differ from more experienced farmers in some key farm management areas. Data were collected by postal survey from farmers of the Salo region in South-Western Finland. Farmers were categorized into three different groups according to a combination of their age and experience. Farmers who were in the early phase of taking over a farm had better education and better networks than their older counterparts. Younger farmers considered their networks to be more important than did their senior colleagues. The early phase farmer group invested significantly more and had more liabilities than the other two groups. Moreover, early phase farmers were the most active at developing their farms. The late phase farmers were the least active, even when they knew they were going to transfer their farm to next generation within the next few years. Farms should be developed continuously in order to improve the viability of whole farming sector.
Keywords: Ma; maatilatalous; viljelijät; farm management; farmers; consolidation phase; multivariate data analysis; networks